(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2017)
The link with the community is a mandate of the Organic Law of Higher Education, in which higher education institutions must create programs and guidelines for linking with society. One of them is through the preparation of the degree studies orÂ dissertations that the students do in the different programs and faculties that the Catholic University Santiago de Guayaquil has. This article aims to reveal what the graduates think of their work, demonstrating the skills and talents learned and apprehended during their courses. During their program, they have had the opportunity to manage projects related to the community, an issue that favours their performance and professionalism. Therefore, it is necessary to unveil their effort by describing the dissertations in the area of the link with the community so as to know who the direct beneficiaries are. The method used is documentary-descriptive. It can be said that when there are direct beneficiaries in the research, there is a direct link, in this case 82%, and this happens when they connect with the pre-professional practices. The remaining 18% of the research work require a direct line to favour this linkage.